1987
DOI: 10.1111/j.1467-9787.1987.tb01184.x
|View full text |Cite
|
Sign up to set email alerts
|

A Hedonic Model of Interregional Wages, Rents, and Amenity Values*

Abstract: This paper develops a general multimarket hedonic model appropriate for a national, interregional study of wages, housing prices, and location-specific amenities. The model encompasses the effects of interregional location, intraurban location, and city size. Typically, hedonic studies focus on a single market such as labor or housing and ignore interactions implicit in a more global compensation mechanism. Examination of the comparative statics of our model indicates that single-market differentials are parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
83
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(85 citation statements)
references
References 10 publications
2
83
0
Order By: Relevance
“…Various studies (for example, Hoehn et al, 1987;Blomquist et al, 1988;or Gyourko and Tracy, 1991) have found convincing evidence that interregional environmental differences are valued and capitalised in the way predicted by the compensating differentials model. However, as Gyourko et al, 1999 conclude: '…recent work….reports the presence of large city-specific error components in the underlying….estimated …local trait prices….it turns out that….the level of imprecision is such that much better descriptions of local amenity and fiscal conditions, plus superior controls for housing, worker and job quality are needed….'…”
Section: Introductionmentioning
confidence: 99%
“…Various studies (for example, Hoehn et al, 1987;Blomquist et al, 1988;or Gyourko and Tracy, 1991) have found convincing evidence that interregional environmental differences are valued and capitalised in the way predicted by the compensating differentials model. However, as Gyourko et al, 1999 conclude: '…recent work….reports the presence of large city-specific error components in the underlying….estimated …local trait prices….it turns out that….the level of imprecision is such that much better descriptions of local amenity and fiscal conditions, plus superior controls for housing, worker and job quality are needed….'…”
Section: Introductionmentioning
confidence: 99%
“…Muellbauer (1974) questions this approach. Other authors use a Box-Cox procedure to find the best fitting form: see Linneman (1980), Quigley (1982), Goodman and Kawai (1984), and Hoehn, Berger, and Blomquist (1987). In the present paper, no transformations are used since almost all of the hedonic determinants here are binary.…”
Section: Methodsmentioning
confidence: 99%
“…Since the work of Rosen (1979), Haurin (1980) and Roback (1982;1988), a growing body of literature has tried to produce theoretically consistent quality-of-life rankings for urban areas by deriving wage and rent differentials via hedonic methods, calculating the implicit prices of locationspecific amenities which are then used as utility valuation weights. 11 While this early literature focuses on interurban differences and treats cities as spatially homogenous entities, extensions by Hoehn, Berger, and Blomquist (1987) incorporate urban structure and intraurban location into the quality-of-life framework and allow for amenity variation both within and across urban areas. In this setting, the relationship between quality of life and urban size remains an empirical matter, ultimately determined by the precise nature of these agglomeration effects and the relative impact of (dis)amenities on production and consumption.…”
Section: Green Cities Urban Sustainability and The Quality Of Lifementioning
confidence: 99%